On the adhesion between thin sheets and randomly rough surfaces - Wang , Anle; Müser, Martin H. (Frontiers in Mechanical Engineering, 2022)
Thin, elastic sheets are well known to adapt to rough counterfaces, whereby adhesive interactions and pull-off stresses σ_p can be significant. Yet, no generally applicable, quantitative guideline has been suggested hitherto as to when a sheet should be considered thin enough to be sticky. Using computer simulations, we find that the dependence of σ_p on surface energy γ has a high and a low-pull-off-stress regime. For randomly rough surfaces, we locate the dividing line at the point, where γ is approximately half the elastic energy per unit area needed to make conformal contact, which is the same ratio as for semi-infinite elastic solids. This rule of thumb bluealso applies to a certain degree for single-wavelength roughness, in which case the transition from low to high stickiness occurs when at the moment of maximum tension contact is not only broken at the height maxima but at the saddlepoints.